Progress and emerging techniques for biomaterial-based derivation of mesenchymal stem cells (MSCs) from pluripotent stem cells (PSCs) - Prakash, Nityanand; Kim, Jiseong; Jeon, Jieun; Kim, Siyeon; Arai, Yoshie; Bello, Alvin Bacero; Park, Hansoo; Lee, Soo-Hong (Biomaterials research, 2023)
The use of mesenchymal stem cells (MSCs) for clinical purposes has skyrocketed in the past decade. Their multilineage differentiation potentials and immunomodulatory properties have facilitated the discovery of therapies for various illnesses. MSCs can be isolated from infant and adult tissue sources, which means they are easily available. However, this raises concerns because of the heterogeneity among the various MSC sources, which limits their effective use. Variabilities arise from donor- and tissue-specific differences, such as age, sex, and tissue source. Moreover, adult-sourced MSCs have limited proliferation potentials, which hinders their long-term therapeutic efficacy. These limitations of adult MSCs have prompted researchers to develop a new method for generating MSCs. Pluripotent stem cells (PSCs), such as embryonic stem cells and induced PSCs (iPSCs), can differentiate into various types of cells. Herein, a thorough review of the characteristics, functions, and clinical importance of MSCs is presented. The existing sources of MSCs, including adult- and infant-based sources, are compared. The most recent techniques for deriving MSCs from iPSCs, with a focus on biomaterial-assisted methods in both two- and three-dimensional culture systems, are listed and elaborated. Finally, several opportunities to develop improved methods for efficiently producing MSCs with the aim of advancing their various clinical applications are described.